From the bottom up : one man's crusade to clean America's rivers - Pregracke, Chad, 1974-; Barrow, Jeff, 1956- (Washington, D.C. : National Geographic, 2007)
Describes one man's grassroots campaign to clean up the nation's rivers and the surrounding environment, without government funding, by removing garbage.
Working the river -- Big job, small boat -- More than I ever imagined -- There's got to be a better way -- From boatloads to barge loads -- That sinking feeling -- Here, there, and everywhere -- Branching out -- Capital improvements -- Katrina -- Coming to a river near you -- Start your own crusade: 13 tips -- Trash statistics, 1997-2005.
Includes index.
Keywords: Water -- Pollution -- United States; Water quality management -- United States; Nonprofit organizations -- United States